Pendampingan Inovasi Produk dan Pemasaran Digital Pangsit Ikan Patin di Poklahsar Barokah - Sari, Fifian Permata; Munajat, Munajat; Dapiokta, Jum (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Providing motivation and technology transfer through assistance with fish dumpling processing innovation, providing assistance through training related to digital marketing and modern packaging design. Research methodology: The method used is participatory. data collection method through direct interviews with respondents. Results: Patin fish products have undergone innovation to become catfish dumplings and catfish bone crackers with original and spicy flavor variants. Product packaging is more modern and attractive, online marketing via the website. Conclusions: Mentoring activities produce more promising business features for Partners to increase their sales turnover. Limitations: This research still uses qualitative data and has not provided quantitative data such as raw material prices, product selling prices and income received by partners. Contribution: This mentoring activity is useful for the Poklahsar Barokah MSME group in Sukosari OKU East Village to develop a catfish processing business. Apart from that, it is also useful for researchers and Baturaja University in community assistance programs.